Sosialisasi dengan Tema Pengenalan Teknologi Tepat Guna Alat Penabur Pupuk Jagung dari Pipa PVC di Desa Bojong Pandan Kecamatan Tunjungteja: Pengabdian - Ita Rosita Wahyiah; Lutfi Septiyadi; Indra Putra; Vidya; Angel Sheripova (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This outreach activity aims to introduce and practice the use of Appropriate Technology (TTG) in the form of a corn fertilizer spreading tool made from PVC pipes as an innovative solution for farmers in increasing fertilization efficiency. The background of this activity is the still low utilization of simple technology among farmers in Bojong Pandan Village, Tunjungteja District, which results in long working hours, large energy, and fertilizer waste. The implementation method includes material counseling, direct demonstrations, and training on the use of tools for farmers. The results of the activity showed that the participants of the outreach were able to understand the working principles and advantages of the tool, such as ease of use, low manufacturing costs, and savings in time and energy in the corn fertilization process. The community's enthusiasm was evident from active participation in the practice and discussion sessions. With the introduction of this technology, it is hoped that farmers will adopt the corn fertilizer spreading tool made from PVC pipes to increase productivity and work efficiency in the agricultural sector.